2023
DOI: 10.3390/diagnostics13193064
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Medicine and Cancer Theragnostics: Basic Concepts

Vasiliki Zoi,
Maria Giannakopoulou,
George A. Alexiou
et al.

Abstract: Cancer theragnostics is a novel approach that combines diagnostic imaging and radionuclide therapy. It is based on the use of a pair of radiopharmaceuticals, one optimized for positron emission tomography imaging through linkage to a proper radionuclide, and the other bearing an alpha- or beta-emitter isotope that can induce significant damage to cancer cells. In recent years, the use of theragnostics in nuclear medicine clinical practice has increased considerably, and thus investigation has focused on the id… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 95 publications
0
3
0
Order By: Relevance
“…The expression of SSTR (Somato Statin Receptor) by NETs (neuro-endocrine tumors) offers a very specific target for diagnostic imaging and therapy. The search for a more efficient theranostic candidate must take into account several parameters, including (1) the peptide sequence/chelator and its affinity for receptor subtypes; (2) the characteristics of the isotope and its SPECT/PET suitability [ 8 , 9 , 10 , 11 , 12 ]. Poletto and coworkers [contribution 3] performed a systematic review of the existing literature in this field.…”
Section: An Overview Of Published Articlesmentioning
confidence: 99%
“…The expression of SSTR (Somato Statin Receptor) by NETs (neuro-endocrine tumors) offers a very specific target for diagnostic imaging and therapy. The search for a more efficient theranostic candidate must take into account several parameters, including (1) the peptide sequence/chelator and its affinity for receptor subtypes; (2) the characteristics of the isotope and its SPECT/PET suitability [ 8 , 9 , 10 , 11 , 12 ]. Poletto and coworkers [contribution 3] performed a systematic review of the existing literature in this field.…”
Section: An Overview Of Published Articlesmentioning
confidence: 99%
“…However, by fully understanding the principles and properties of nuclear medicine therapeutics, we believe that they are effective. Furthermore, through an investigation of the dynamics and pathological analysis of nuclear medicine, it has been shown that the side effects are not significantly different from those of other drugs [12][13][14][15]. Nuclear medicine therapeutics are expected to become new treatment options for patients for whom existing therapeutic drugs are not suitable.…”
Section: Introductionmentioning
confidence: 99%
“…Utilizing the same radionuclide or pairs of chemically identical radioisotopes with similar half-lives and complementary emissions has proven to be an efficient strategy for theranostic studies. These shared features ensure the same behavior for both diagnostic and therapeutic radiotracers, a crucial factor contributing to the success of the analysis [ 21 , 22 , 23 , 24 ]. An illustrative example is the utilization of [ 68 Ga]Ga-DOTA-TOC, which extends beyond diagnostic applications and is also investigated in theranostic use, in conjunction with its therapeutic partner [ 177 Lu]Lu-DOTA-TATE (Lutathera ® ), known for its significant binding affinity for somatostatin receptors (SSTR) [ 12 ].…”
Section: Introductionmentioning
confidence: 99%